Application of 2D Electrical Resistivity Tomography in Landfill Site: A Case Study of Iku, Ikare Akoko, Southwestern Nigeria. (28th October 2013) - Chibueze Okpoli, Cyril
Abstract : 2D resistivity tomography was used inx, y, andz directions to delineate the extent of leachate plumes around a solid waste landfill in Ikare Akoko, Ondo State, behind the secretariat. I access the geometry and depth contamination extent of the landfill repository using dipole-dipole method and Global positioning system to ascertain the image of the subsurface and the position at the earth surface. The study area is underlain by Precambrian basement rocks. Quantitative interpretation of pseudosection results shows that in traverse 1, stations 7, 8, and 9 form a conductive path at the depth of 1–10 m and penetrate to depth of 25 m; the second traverse shows a layer of highly conductive structure extending diagonally across the study area, while the third traverse is partly conductive and largely resistive due to its closeness to fresh basement rocks. The 2D structure has shown various conductive path ways via fractures and openings, thus, contaminating the groundwater. I recommend that further geochemical analysis of the water should be done to ascertain the level of contamination.